Baby assassins 2 [videorecording (Blu-Ray)] - Sakamoto, Hugo; Takaishi, Akari; Izawa, Saori; Tee, Joey; Hamada, Tatsuomi (Well Go USA Entertainment, 2024)
After being suspended from their agency due to a rule violation, two highly skilled teenage assassins are forced to get 'real' jobs to make ends meet. But while the elite duo is forbidden from executing targets or enemies under any circumstances, two aspiring rival hitmen decide to eliminate the competition while they're vulnerable leading to a lightning-fast showdown between trained killers.